Guide to Research and Development (R&D) for Undergraduate Students of Educational Technology - Frezy Paputungan; Iwan B. Jassin; Abd. Rahman K. Ma'ruf (JCI Publisher, 2026)
Research is the systematic and planned process of collecting, processing, and analyzing data in accordance with scientific principles to seek truth, solve problems, or discover new knowledge. Conducting research often serves as a final project for undergraduate students to complete their studies; for Educational Technology undergraduates, in particular, development research is highly recommended. Development research—or Research and Development (R&D)—is a scientific method used to create new products or improve existing ones, as well as to test their effectiveness. These products may take the form of media, models, modules, or tools. Specifically for Educational Technology undergraduates, this type of research involves a scientific approach to designing, producing, and testing the feasibility of instructional products—such as interactive media, learning models, or digital modules—to address learning challenges. The primary objective of R&D for Educational Technology undergraduates is to produce instructional products that are valid, practical, and effective in solving learning problems and enhancing the quality of the learning process and performance. The benefits of such research include improved skills in creating instructional products, the ability to solve real-world learning problems, and the development of a professional portfolio.